Status And Legal Relationship Between Plasma Farmers And Core Companies In Partnership Agreements (Case Study At Pt. Sierad Produce, Tbk Div. Partnership) - Evita Vibriana Wulandari; Faisal Santiago; Suparno Suparno (Jurnal Indonesia Sosial Sains, 2023)
In this study, the authors used empirical legal research methods based on primary data sources based on field research on partnership agreements, interviews with users. Secondary data is literature study by reading and studying and understanding literature books as well as the knowledge gained during lectures. In addition to conducting interviews and observations. The analysis used was descriptive qualitative, namely a data analysis method that classifies and selects data obtained from field research according to its quality and truth, then linked with theories, principles and legal principles obtained from literature studies so that answers are obtained. formulated problem. Theory used: 1. Grand Theory (Theory of Legal Relations); According to R. Soeroso: Legal relationship is a relationship between two or more legal subjects. In this legal relationship, the rights and obligations of one party deal with the rights and obligations of the other party. That the law regulates the relationship between one person and another, between people and society is regulated by law. Whoever disturbs or ignores this relationship, then he can be forced by law to respect it. So every legal relationship has two aspects: the aspect of "bevoegdheid" (power/authority or right) with its opponent "plicht" or obligation. The authority granted by law to legal subjects (persons or legal entities) is called "rights". 2. Middle Theory (Theories in Contract Law); Freedom of contract is a reflection of the development of free market ideas pioneered by Adam Smith. Adan Smith, with his classical economic theory, underlies the thinking of Jeremy Bentham, known as Jeremy Benthan's utilitarianism, in his book Ïntruction to the Morals and Legislation, which argues that law aims to realize only what is beneficial to people. 3. Utilitis Theory: the purpose of law is: to guarantee the maximum happiness for as many people as possible. Certainty through law for individuals is the main goal of law. In this case Bentham's opinion is emphasized on things that are useful and general in nature. Applied Theory (Partnership Pattern); The concept of economic democracy in Pancasila does not allow free fighting between the strong and the weak, but is more directed towards harmony and mutual support between economic actors, this creates an obligation for the government to regulate and establish legislation.